The Transformation of Gala and Mawah: Towards the Sharia Gala Bank Microfinance Model in Aceh - Hamid, Wardiah; Sumardi, Dedy; Suarsana, I Made; Dachlan, Muhammad; Hamsiati, Hamsiati (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The Acehnese society has long practiced customary economic arrangements such as gala (pawning) and mawah (profit-sharing). However, the traditional gala practices are frequently exploitative and inconsistent with the Sharia principles, as lenders exercise full control over collateralized productive assets. In addition, the potential of mawah as a cooperative economic mechanism has not been fully realized. This qualitative study examines the transformation of these customary practices into sustainable Sharia-based microfinance institutions through a case study of their implementation in Southwest Aceh. Data were collected through observations and in-depth interviews. The findings indicate that KSPPS Baitul Qiradh Gala Muamalah, commonly known as the “Gala Bank,” has initiated a revitalization of local economic wisdom grounded in Sharia principles. A fundamental transformation is evident in the gala practice through the application of a rahn (Sharia pawn) contract, whereby the institution holds only the collateral, while productive assets, such as rice fields, remain under the management of their owners. This arrangement enables farmers to continue agricultural production and generate income. For working capital financing, the institution employs a mudharabah (profit-sharing) contract with a flexible post-harvest repayment system. The “Gala Bank” model has successfully transformed previously harmful practices into equitable, farmer-empowering, and Sharia-compliant transactions. Consequently, this initiative demonstrates how traditional economic practices can be effectively adapted into a modern, sustainable economic framework rooted in local culture, serving as a model for community-based economic development.